2018
DOI: 10.1074/jbc.m117.809780
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146 and cell trauma down-regulate expression of the psoriasis-associated atypical chemokine receptor ACKR2

Abstract: Chemokines are the principal regulators of leukocyte migration and are essential for initiation and maintenance of inflammation. Atypical chemokine receptor 2 (ACKR2) binds and scavenges proinflammatory CC-chemokines, regulates cutaneous T-cell positioning, and limits the spread of inflammation in vivo. Altered ACKR2 function has been implicated in several inflammatory disorders, including psoriasis, a common and debilitating T-cell–driven disorder characterized by thick erythematous skin plaques. ACKR2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Along with it, the presence of α 2 β1 integrin in the suprabasal epidermal layers (normally it is in basal epidermal layer) [98,99]; increased expression of S100A7 (psoriasin) and S100A15 (koebnerisin) in the epidermis [26]; predominance of CD4 + cells over the CD8 + T cells in the epidermis [5]; increase in chemokines viz. CXCL8 and CCL20 [30], down-regulation of mechanosensitive polycystin 1 protein [27], ACKR2 [28], and ionotropic NMDARs on the keratinocytes [114] also contribute in the development of secondary psoriatic lesions following skin injury.…”
Section: Summarized Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with it, the presence of α 2 β1 integrin in the suprabasal epidermal layers (normally it is in basal epidermal layer) [98,99]; increased expression of S100A7 (psoriasin) and S100A15 (koebnerisin) in the epidermis [26]; predominance of CD4 + cells over the CD8 + T cells in the epidermis [5]; increase in chemokines viz. CXCL8 and CCL20 [30], down-regulation of mechanosensitive polycystin 1 protein [27], ACKR2 [28], and ionotropic NMDARs on the keratinocytes [114] also contribute in the development of secondary psoriatic lesions following skin injury.…”
Section: Summarized Discussionmentioning
confidence: 99%
“…Using in silico and in vitro studies, it was shown that miR-146b directly binds to the 3 -UTR region of ACKR2 gene, leading to decreased expression of ACKR2 in keratinocytes. Accordingly, it may be suggested that the changes in the epigenetic regulation (via miR-146b) of an atypical chemokine receptor with the down-regulation of the expression of latter protein may be responsible for the inappropriate and excessive immune response during the Koebner phenomenon in psoriasis [28].…”
Section: Down-regulation Of Ackr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent novel studies have proposed a molecular mechanism for KP in psoriasis [ 8,9 ] . Researchers demonstrated that cell trauma downregulates the expression of the atypical chemokine receptor 2 (ACKR2), a "chemokine scavenger" that limits infl ammation in psoriasis, potentially via upregulation of microRNA-146b [ 9 ] . Thus, the physical trauma in HFMD lesions could be the fi nal trigger that leads to psoriatic plaque development in an infl ammatory setting.…”
Section: Department Of Dermatology Cathay General Hospital Taipeimentioning
confidence: 99%
“…According to Pivarsci et al , due to Toll-like receptor (TLR) ligands, miR-146 is persistently increased in keratinocytes, downregulating the expression of inflammatory chemokines including IL-8 and C-C motif chemokine ligand 20 ( 23 ). Consequently, miR-146a decreases TLR-dependent epidermal inflammation via the IL-1 receptor-associated kinase-1 and TNF receptor-associated factor 6 pathways, which mediate the IL-17A signaling to NF-κB and the recruitment of inflammatory cells ( 24 27 ) ( Fig. 4 ).…”
Section: Micrornas Involved In Psoriasismentioning
confidence: 99%